Successful Management of Extensor Tendon Injury in the Hind Limb of a Buffalo Bull using External Coaptation - Baltej Singh; Akashdeep Singh Hundal; Vandana Sangwan (The Indian Veterinary Journal, 2024)
The report describes the successful management of extensor tendon injury in a 2.5 year old, 480kgs buffalo bull. A village common bull was presented in emergency hours with a 3 side extensive cut wound proximal to fetlock region (involving extensor tendons) with a wire-fence while fighting with another bull. The major bleeders were ligated under sedation and skin sutures were applied. To avoid knuckling of the fetlock, the limb was bandaged with heavy cotton layering and a straight aluminium splint on the posterior aspect. The bull showed full weight bearing by day 14 with coaptation, although the hoof of the affected limb showed a slight split due to a lower extensor tendon injury.